Educação em consumo, na linguagem dos quadrinhos : uma análise crítica da revista Turma da Mônica Jovem - Setubal, Flávia Meneguelli Ribeiro (2015)
Created in August 2008, the comic book "Monica Teen", or TMJ, as it is known by its readers, has manga style and brings the same characters residents of Limoeiro neighborhood, now, teenagers that have very different characteristics of the traditional group. This research sought to develop a critical analysis of TMJ within the theoretical and methodological assumptions of discursive semiotics, seeking to answer the questions: how the issue of consumption is appropriated by the comic book? What enunciation strategies are used to include the youth public into its discourse? The literature review makes a triangulation of the guiding concepts of the study: Comics, Children's Consumption and Semiotics, bringing, in the center of the triangle, Education, the research’s main area of expertise and connector of the three other fields. We conducted a semiotic analysis of a corpus of seven editions of TMJ that brought as main theme issues related to the contemporary consumer society, from a universe of comic books published from 2012 to 2014. Among the pre-established consumption categories or the ones that emerged from TMJ discourse, behold: the conscious consumption, the conspicuous consumption, the moralist consumption and the consumption of media culture. Through the focus group technique, we developed a conversation with TMJ readers, trying to understand how is the apprehension of the consumption issue by them, and also what impacts this apprehension has to increase the attractiveness of the publication, among other specific objectives investigated at this meeting. While conducting three groups entitled Beginners Readers, Regular Readers and Sporadic Readers, we could group them into two categories related to the field of consumption and of semiotics. The group of Belonging knows and interacts with the comic book, in depth, providing a sensitivity adjustment between enunciatee (reader) and the enunciator (comic book), with features of "appear to be and be." The Emulation group wants to belong to the group of assiduous readers, but once they do not have the features to do so, they seek through imitation, within a regime of "appear to be, but do not be." The survey results indicate that consumption is frequently present along the TMJ plots, having appeared as the main theme, in more than half of the comics analyzed. Still, it can be considered as the central theme of the stories, especially when the comic book uses its plasticity in the characters and stories environments’ figurativization to spread a world of consumption to these children and adolescents readers. Although comics that fit into the categories of conscious consumer and moralist consumption seek to transmit some advice and lessons for its readers, the categories of conspicuous consumption and consumption of media culture, treated uncritically and, sometimes, irresponsible, are the ones that have a higher degree of apprehension by the reader, increasing the attractiveness of the comic book. Among other findings, we can say that the TMJ discourse uses simple narrative (linear and less complex), as well as figurative and repetitive themes, offering little debate and reflection to its readers, being a speech of reproduction, without deepening, of these children and adolescent day-to-day. Despite speaking about them and for them, it does not include many relevant themes to their universe.